Green Synthesis of Silver Nanoparticles Using Tamarind (Tamarindus indica) Leaf Extract and Their Application as an Antibiofilm Agent in Pseudomonas aeruginosa Infected Wounds - Emma Jayanti Besan; Muhammad Nurul Fadel; Cut Intan Annisa Puteri; Dzukharian Munandar; Putri Tri Hartini (CV. Get Press Indonesia, 2025)
Multidrug-resistant Pseudomonas aeruginosa poses a significant challenge in chronic wound management due to its robust biofilm formation and antibiotic resistance. Green-synthesized silver nanoparticles (AgNPs) using Tamarindus indica (tamarind) leaf extract offer an eco-friendly and effective approach to combat these infections. The bioactive phytochemicals in tamarind leaves function as both reducing and stabilizing agents, producing biocompatible AgNPs with potent antimicrobial and antibiofilm activities. These nanoparticles disrupt bacterial membranes, generate reactive oxygen species, inhibit virulence factors such as pyocyanin, and compromise biofilm integrity. Incorporation of tamarind-derived AgNPs into hydrogels or composite wound dressings further enhances wound healing by maintaining a moist environment and providing sustained antimicrobial release. Although in vivo studies specifically using tamarind AgNPs against P. aeruginosa are limited, evidence from other plant-derived AgNPs supports their promising potential for treating biofilm-associated wound infections. Green synthesis using tamarind thus represents a sustainable strategy for developing next-generation antimicrobial wound therapies.